Influence of proprioceptive training on fencing athlete’s performance: a clinical trial - Vasconcelos, Gabriela; Cini, Anelize; Grazioli, Rafael; Minozzo, Felipe; Lima, Cláudia (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: Fencing is an agility sport and is characterized by a combination of short and frequent high intensity movements. Proprioceptive training demonstrates a positive effect on athletes’ performance. It is effective in increasing dynamic balance by reducing ankle muscle reaction time that stabilize joint. Objective: The aim of this study was to verify influence of a 12-week proprioceptive training program on ankle instability, jumping performance and ankle muscle’s reaction time during Lunge in fencing athletes. Method: The study was a clinical trial, non-randomized, with 19 fencing athletes from 14-35-year-old, divided in intervention group (n=10) and control group (n=9). The study was performed in four stages: familiarization of jump performance; pre-intervention; intervention and post-intervention. At pre-intervention was evaluated jump performance, ankle muscle reaction time and functional ankle instability. At the intervention, athletes performed 30 minutes of proprioceptive training for 12 weeks, three times a week. At post-intervention, the same pre-intervention tests were performed. Data were presented in mean and standard error, submitted to the Generalized Estimates Equations test with Bonferroni post hoc. The level of significance was 0,05. Results: Jump performance decreased significantly in both groups. Anterior tibial muscle reaction time did not differ neither in any of groups, nor in any of legs. The peroneus longus and lateral gastrocnemius reaction time decreased significantly in both groups. Regarding functional ankle instability, athletes had instability at pre- and post-intervention time. Conclusion: Proprioceptive training program was not able to improve jump performance, nor to decrease ankle muscle reaction time or improve athletes’ perception of ankle stability.